Denominal verbs in English and Mandarin from a cognitive perspective / Bai Rong - Bai, Rong (2014)
A linguistic phenomenon of denominal verbs is pervasive in both English and Mandarin. Many Chinese and foreign linguists have illustrated or analyzed this phenomenon. However, most of the previous research has explored the motivation of denominal verbs from semantic, syntactic or pragmatic perspectives. In order to look into the phenomenon, this study adopts a cognitive perspective to probe the phenomenon, arguing that denominal verbs are the product of certain construal operations, and that the semantic meanings of denominal verbs are dynamic, open, and based on the specific linguistic environment. Data in this research mainly come from relevant literature, dictionary and newspaper. Other public internet sources are also used in this study. From the comparison and analysis of English and Mandarin data, we find that the general distribution of the major kinds of metonymic denominal verbs in English is in consistency with that in Mandarin, and the mechanism of English metaphoric denominal verbs is also similar with that of Mandarin ones. However, due to the influence of cultural elements and different ways of thinking, many discrepancies also exist among English and Mandarin denominal verbs. This study has also supported the two basic tenets in cognitive linguistics: meaning is mental entities in conceptual space, and the conceptual structure of meaning is embodied and motivated by usages: the content of the conceptual structure draws upon an open-ended and encyclopedic knowledge. Key words: denominal verbs, cognitive grammar, metaphor and metonymy